Implementasi Metode Finger Painting dalam Peningkatan Kreativitas Anak Usia Dini di TK Islam Masa Depan Ketapang Desa Menceh Kecamatan Sakra Timur Tahun Ajaran 2021/2022 - Qusyairi, Lalu A. Hery; Nurmah, Nurmah (ARZUSIN, 2022)
A study entitled Implementation of the Finger Painting Method in Improving Early Childhood Creativity in the Future Islamic Kindergarten of Ketapang in the 2021/2022 Academic Year has been carried out. This study aims to increase the creativity of Early Childhood using the Finger Painting method. Children's creativity can be developed by doing a variety of interesting activities, the latest learning models, providing learning media that can attract children's attention in the learning process so as to make children more excited. This research is a Classroom Action Research (CAR) using qualitative methods. The research data were obtained by using observation and documentation techniques. The increase in the creativity of students is indicated by the increasing number of positive (yes) columns that are filled in for each indicator set. The research obtained is the indicator "Making simple pictures using finger painting" from 16 students, 7 children (43.75%) positive column (yes) filled in the pre-cycle, 11 children (68.75%) column in the first cycle and 13 children (81.25%) column in cycle II. The indicator "Creating pictures using finger painting" from 16 students, 1 child (6.25%) positive column (yes) filled in the pre-cycle, 8 children (50%) column in the first cycle and 13 children (81.25 %) column in cycle II,. The indicator "Making pictures with finger painting according to the teacher's example" of 16 students 4 children (25%) positive column (yes) filled in the pre-cycle, 9 children (56.25%) column in the first cycle and 13 children ( 81.25%) column in cycle II. Based on the results of this study, it can be concluded that there was a lot of improvement from pre-cycle to cycle I from the indicator "Making simple images using finger painting" which was 25% then from cycle I to cycle II as much as "12.5%". Then on the indicator "creating images using finger painting" which is 43.75% then from cycle I to cycle II as much as 31.25%. The indicator "making pictures with finger painting according to the teacher's example" is 31.25%, in the first cycle to the second cycle it is 25%. Based on the results of the study, it can be concluded that the effectiveness of using the finger painting method can increase children's creativity in Islamic Kindergarten Future Ketapang, Menceh Village, Sakra Timur District.